Mycotoxin Aptasensing Amplification by using Inherently Electroactive Graphene‐Oxide Nanoplatelet Labels. Issue 5 (18th February 2015) - Loo, Adeline Huiling; Bonanni, Alessandra; Pumera, Martin
Abstract We develop an electrochemical aptasensor for ochratoxin A (OTA) by utilizing graphene‐oxide nanoplatelets (GONPs) as electroactive labels. OTA aptamer (OTA‐apt), which serves as the recognition element, was first immobilized onto the electrode surface before the modified electrode underwent exposure to OTA. Subsequently, incubation with GONPs was performed and the nanoplatelets conjugated to the immobilized OTA‐apt through π–π interactions. The principle of detection lies in the ability of these nanoplatelets to be electrochemically reduced, thereby producing a well‐defined reduction peak that was then employed as the analytical signal. The fabricated aptasensor is capable of detecting OTA in the concentration range of 310 fM to 310 pM, with good selectivity against common interferences. The obtained results from this study have the potential to contribute towards the aim of developing a biosensor for OTA, with high selectivity and sensitivity.